Increasing ecological heterogeneity can constrain biopesticide resistance evolution - Mangan, Rosie; Bussière, Luc F.; Polanczyk, Ricardo Antônio [UNESP]; Tinsley, Matthew C. (Elsevier, 2023)
Microbial biopesticides containing living parasites are valuable emerging crop protection technologies against insect pests, but they are vulnerable to resistance evolution. Fortunately, the fitness of alleles that provide resistance, including to parasites used in biopesticides, frequently depends on parasite identity and environmental conditions. This context-specificity suggests a sustainable approach to biopesticide resistance management through landscape diversification. To mitigate resistance risks, we advocate increasing the range of biopesticides available to farmers, whilst simultaneously encouraging other aspects of landscape-wide crop heterogeneity that can generate variable selection on resistance alleles. This approach requires agricultural stakeholders to prioritize diversity as well as efficiency, both within agricultural landscapes and the biocontrol marketplace.
Keywords: agroecology; crop protection; genotype-by-environment interactions; integrated pest management; landscape diversity; sustainable agriculture